2016
DOI: 10.1136/bmj.h6895
|View full text |Cite
|
Sign up to set email alerts
|

Patient choice in opt-in, active choice, and opt-out HIV screening: randomized clinical trial

Abstract: Study queStion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
95
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 45 publications
3
95
1
Order By: Relevance
“…Although this study was not designed to capture the number of patients who opted out, most participants stated that patients rarely declined (except for people who did not want to have blood tests done at all or reported that they were HIV positive). Studies from diverse settings around the world have shown high patient acceptance of opt-out HIV testing (Haukoos et al 2008;Wilson d'Almeida et al 2013;Montoy et al 2016). This is the first Australian study to demonstrate that marginalised patients are accepting of the opt-out method.…”
Section: Discussionmentioning
confidence: 94%
“…Although this study was not designed to capture the number of patients who opted out, most participants stated that patients rarely declined (except for people who did not want to have blood tests done at all or reported that they were HIV positive). Studies from diverse settings around the world have shown high patient acceptance of opt-out HIV testing (Haukoos et al 2008;Wilson d'Almeida et al 2013;Montoy et al 2016). This is the first Australian study to demonstrate that marginalised patients are accepting of the opt-out method.…”
Section: Discussionmentioning
confidence: 94%
“…[23] To maximise test acceptance and subsequent new HIV diagnoses, evidence must be used for decisions about the best way to conduct testing procedures. [38] The SA government is therefore urged to move toward an opt-out testing system in preference to the current optin system.…”
Section: Discussionmentioning
confidence: 99%
“…[19] A randomised controlled trial (RCT) of 48 000 ED patients in the USA randomised patients to one of the three arms (opt-in, active choice, and opt-out): 38%, 51%, and 66%, respectively, supported opt-out consent as being superior. [23] A 2011 study utilising comparative time-sequencing found a 78% uptake of HIV testing in the opt-out group compared with 63% in the traditional counsel-and-test method. [20] Rates of acceptance approaching 86% were found in the Deep South of the USA, where the HIV prevalence and TB rates are the highest.…”
Section: Hiv Testing In Lmicsmentioning
confidence: 99%
“…In a linked paper (doi:10.1136/bmj.h6895), Montoy and colleagues examine this important matter. 6 In 2006 the US Centers for Disease Control and Prevention (CDC) revised its HIV screening recommendations in clinical settings, calling for routine, non-targeted (non-risk based) screening using opt-out consent, whereby patients are told that they will be tested unless they decline. 7 The CDC chose opt-out consent to improve acceptance of HIV testing, on the basis of its early successes among pregnant women in labor and delivery units.…”
mentioning
confidence: 99%
“…6 The authors randomized 4800 emergency department patients, who were aged 13-64 years, had a variety of medical complaints, and were not already known to be infected with HIV, to one of the three arms, with acceptance of a test as the outcome. Across the three study groups-opt-in, active choice, and opt-out-test acceptance percentages were 38%, 51%, and 66%, respectively, supporting opt-out consent as the superior method.…”
mentioning
confidence: 99%